Screening of organochlorine insecticides (DDT and heptachlor) in dry fish available in Bangladesh - Md. Nurul Huda Bhuiyan; Habibur Rahman Bhuiyan; Matiur Rahim; Kabir Ahmed; K. M. Formuzul Haque; Md. Tariqul Hassan; Md. Nazrul Islam Bhuiyan (Bangladesh Pharmacological Society, 2008)
The concentrations of organochlorine insecticides DDT and heptachlor were investigated to estimate the current status of insecticides used in dry fish. The most popular dry fish- ribbon fish (Chhuri), shrimp (Chingri) and bombay duck (Loittya) were selected for this study and these dry fishes were collected from different markets of Dhaka and Chittagong. The range of DDT used in all the samples was 3.038 ppb to 874.966 ppb. The range of DDT in ribbon fish 131.611 ppb to 149.430 ppb, in shrimp 3.038 ppb to 318.206 ppb and in bombay duck 61.918 ppb to 874.966 ppb was found. The range of heptachlor used in all the samples was 0.682 ppb to 5.464 ppb. The range of heptachlor in ribbon fish 1.710 ppb to 2.306 ppb, in shrimp 0.682 ppb to 3.806 ppb and in bombay duck 1.762 ppb to 5.464 ppb was found. The heptachlor was not found in ribbon fish (CTG-2), shrimp (DHK-2 and CTG-1) and bombay duck (DHK-1). The concentration of heptachlor in dry fish compare to DDT was found too much less.